Tribological Behavior of Novel CNTs-Based Lubricant Grease in Steady-State and Fretting Sliding Conditions - Adolfo Senatore (MDPI AG, 2021)
The tribological behavior of novel 7.5 wt% carbon nanotube-based lubricant greases in PAO (polyalphaolefin) oil with and without 1.0 wt% MoS2, together with several other commercial greases such as calcium, lithium, were studied. The test results showed a marked reduction of frictional coefficient achieved by the CNTs based grease samples with an average benefit of around 30% compared to conventional greases. The steady state test under 1.00 GPa average contact pressure in a mixed lubrication regime and the fretting test showed the best results in terms of friction reduction obtained by CNTs greases. Steady state tests at higher average contact pressure of 1.67 GPa proved to have a lower friction coefficient for CNTs grease containing MoS2; otherwise CNTs grease without MoS2 showed an average value of CoF comparable to calcium and lithium greases, both in a boundary and a mixed regime. The protection against wear, a considerable decrease (−60%) of reference parameter was measured with CNTs grease with MoS2 (NLGI 2) in comparison with the worst conventional grease and −22% in comparison with the best conventional grease. The data indicated that our novel carbon nanotube greases show superior tribological properties and will have promising applications in the corresponding industry.